Impact Of Interactive Control In Improving Academics' Performance: Mediating Role Of Fairness - Yani, Indah; Nazaruddin, Ietje (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
This study aims to empirically examine the direct and indirect effects of interactive control on performance by analysing the role of justice as an intervening variable. This research uses a survey approach by distributing questionnaires directly or online. The research sample obtained was 383 academics at universities throughout Indonesia. Data analysis was carried out using structural equation modelling. The results showed that interactive control has no direct effect on performance. However, interactive control indirectly affects academic performance through fairness. This suggests the importance of improving fairness in effective performance measurement to improve academic performance. The novelty of this study lies in equity as an intervening variable in the relationship between interactive control and performance. The findings of this study provide practical insights for higher education management to implement an interactive control approach that can increase the sense of fairness towards implementing performance measurement systems to impact academic performance positively.